Cardiovascular responses to tilting in Type 2 Diabetic patients - Rejwana, Iffat; Rimi, Sadia Afrin; Sultana, Shamima; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2020)
Background: Diabetes mellitus (DM) is a disorder with a debilitating effects on cardiac autonomic control. Multiple major cardiovascular risk factors associated with DM led diabetic patients at high risk of Cardiovascular Disease. Objective: To assess cardiovascular responses to tilting in Type 2 Diabetic patients (T2DM) with normal and abnormal autonomic function test. Methods: This experimental study was conducted on 60 patients of T2DM. Among them, 30 patients were with normal cardiovascular reflex test (group DN) and 30 patients were with abnormal test (group DA). Thirty(30) apparently healthy subjects with similar age and sex without any physical illness were enrolled as control. Tilt table test of all subjects was done by tilting at 60° for 10 min by using a motorized tilt table. Cardiovascular response to tilt test was assessed by calculating D Heart rate (Acceleration index and Brake index); DSBP (SBP 30s-0 and SBP1 min -0), DDBP (DBP 30s-0 and DBP1 min -0) after tilting. For statistical analysis, one-way ANOVA followed by Bonferroni post hoc was used. Results: In this study, the Acceleration index was significantly higher in patient group DN compared to control and DA(p<0.001). But the Brake index was significantly (p<0.01, p<0.05) lower in both group of patients compared to control. In addition, SBP 30sec-0 and SBP1 min-0 were significantly higher in DA than those of control and DN.DBP 30sec-0 and DBP1min-0 were significantly (p<0.001) lower in DA patients compared to DN and control. Conclusion: This study concluded that cardiovascular response to tilting was weak in T2DM patients and it was greatly affected in T2DM patients with abnormal autonomic function test. J Bangladesh Soc Physiol. 2020, December; 15(2): 78-84